PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR) DAN INTELLECTUAL CAPITAL (IC) TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERASI - Liani, Yolan; Wardhani, Rulyanti Susi; Sumiyati, Sumiyati (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2024)
Firm value is important because high company value will bring great prosperity to shareholders. Firm value describes company performance which can influence investor perceptions. High firm value not only reflects the company's current performance, but also shows market confidence in the company's prospects in the future. This study aims to determine and analyze the effect of Corporate Social Responsibility (CSR) and Intellectual Capital (IC) on firm value which is moderated by profitability. The sampling technique of this study used purposive sampling and based on established criteria obtained as many as 33 manufacturing companies listed in BEI in 2021-2023. This study adopted a quantitative approach with data analysis methods in the form of descriptive statistical analysis and panel data regression analysis. The result show that Corporate Social Responsibility (CSR) has a positive effect on firm value, Intellectual Capital (IC) has no effect on firm value, profitability is able to moderate the effect of Corporate Social Responsibility (CSR) on firm value, and profitability is able to moderate the effect of Intellectual Capital (IC) on firm value.